Determinants of teachers' practice of infusing Islamic manners (adab) in the secular classrooms in the Southern Thailand - Mohd Ali, Hairuddin; Nordin, Mohamad Sahari; Sa-U, Samsoo (2011)
The objectives of this research are to develop, examine and validate a model of infusing Islamic manners (adab) in the secular classroom (iMIS). A proposed model consists of endogenous variables (teacher attributes and perceived support) and exogenous variables (teachers’ performance in iMIS). A survey instrument was administered to 561 both Malay and non- Malay speaking Muslim teachers at public primary schools in 6 provinces of Southern Thailand. The structural equation modeling (SEM) is used to validate and test the model fit to the empirical data. The results show that the four proposed teacher attributes (self-efficacy, values, Islamic work ethic, and organizational commitment) and two factors of teachers’ perceived support (peer and curriculum support) directly influence to their performance in iMIS.